Discourse on Fiduciary Guarantee Execution’s Arrangement After the Constitutional Court Decision Number 18/PUU-XVII/2019: A Deterioration? - Putrawan, I Putu Reinaldy; Sudiarawan, Kadek Agus (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
This research has a goal in terms of knowing the arrangements for Fiduciary Guarantees as a national legal instrument, to find out the procedures for executing fiduciary guarantee objects, as well as those disclosed as a result of the issuance of the Constitutional Court Decision Number: 18/PUU-XVII/2019. This study uses a normative legal research method with a statutory approach and an analytic and conceptual approach. The results of this study indicate that fiduciary guarantees as national guarantee legal instruments have been regulated through the Fiduciary Guarantee Act as a legal umbrella in the procedure for implementing fiduciary guarantees. Regarding the procedure for executing fiduciary guarantees, it is specifically regulated in the Fiduciary Guarantee Law by using executorial titles, through public auctions, and also underhand or private sales. However, after the Decision of the Constitutional Court Number: 18/PUU-XVII/2019 raises a legal implication for the execution procedure in terms of buying a default based on an agreement with the debtor who voluntarily surrenders the object and the execution procedure must be based on an agreement and there is already legal remedies against fraudulent breach of contract actually imposed on the creditor's position.